PTH-165 Hexane extracts of calophyllum brasiliense inhibit the development of gastric preneoplasia in helicobacter felis infected ins-gas mice. (22nd June 2015) - Lemos, L; Miyajima, F; Martins, D Tabajara de Oliveira; Pritchard, DM; Burkitt, MD
Abstract : Introduction: Calophyllum brasiliense is a tropical hardwood tree native to Latin America. Indigenous populations have used extracts from the stem bark of this tree to treat gastrointestinal symptoms for generations. In previous studies we demonstrated that a hexane extract of Calophyllum brasiliense stem bark (HECb) protects against an acidified ethanol model of gastric ulceration in Swiss-Webster mice. We hypothesised that HECb would also inhibit the gastric epithelial pathology, including gastric preneoplasia that is induced by Helicobacter infection. To investigate this we have used the established hypergastrinaemic INS-Gas, H. felis infection model. Method: Groups of 6 male, 6 week old INS-Gas mice were colonised with H. felis by oral gavage. Between 2 weeks after colonisation and the end of the procedure their drinking water was supplemented with 2% Tween 20, HECb 83.3 mg/L (lHECb) or HECb 333.3mg/L (hHECb). Equivalent uninfected control groups were also studied. Animals were culled 6 weeks after H. felis colonisation. Gastric mucosal samples were taken for histology and protein extraction. Preneoplastic pathology was quantified using established histological criteria. Gastric epithelial cell turnover was quantified by immunohistochemistry for Ki67 and active-caspase 3. Cytokines were quantified using electrochemiluminescence assays. Results: H. felis infected mice treated with Tween 20 exhibited increased gastric atrophy scores than uninfected mice treated with Tween 20 (mean atrophy score 5.6+/-0.87 SEM vs 2.2+/-0.58, p < 0.01). The same pattern was observed following lHECb. Following hHECb, atrophy scores were lower in infected mice, and no significant difference was observed between these infected and uninfected mice (4.0+/-0.45 vs 1.8+/-0.86). Gastric epithelial apoptosis was not altered by H. felis or HECb administration. Compared to uninfected mice, gastric epithelial cell proliferation was increased 2.8 fold in infected, Tween 20 treated mice (p < 0.01). Administration of either lHECb or hHECb reduced proliferation indices to similar levels seen in uninfected mice. Cytokine evaluation demonstrated a Th 17 polarised response to H. felis infection and decreased abundance of IFN-γ, IL-6 and TNF in the infected mice administered hHECb (70% (p < .01), 67% (p < .01) and 41% (p < 0.05) reduction vs Tween 20 respectively). Conclusion: HECb modulates gastric epithelial pathology following H. felis infection in INS-Gas mice. The extract influences both epithelial cell turnover and cytokine production. Further studies are indicated to dissect the mechanisms underlying these observations, and to identify the biologically active constituents of HECb. Disclosure of interest: None Declared.